Alterations in the metabolism of tryptophan in patients with chronic hepatitis C six months after pegylated interferon-α 2a treatment. (November 2018) - Pawlowski, Tomasz; Malyszczak, Krzysztof; Inglot, Małgorzata; Zalewska, Małgorzata; Radkowski, Marek; Laskus, Tomasz; Pawlak, Dariusz
Highlights: IDO activity was significantly increased in comparison to baseline during PEG-IFN-α2a treatment. IDO activity and TRP concentrations were significantly associated over time with the total MADRS score. Six months after PEG-IFN-α2a treatment IDO activity and KYNA concentration were significantly higher compared to baseline. Abstract: Background: Risk of depression and suicide in patients on interferon remains also after the treatment, the pathogenesis of which is still unclear. We aimed to determine the influence of the PEG-IFN-α2a on tryptophan metabolism along the kynurenine pathway during treatment and up to 6 months after the end of treatment. Methods: We evaluated 101 patients with chronic hepatitis C treated with PEG-IFN-α2a, and 40 controls, so as to determine the activation of indolamine 2, 3-dioxygenase (IDO) and tryptophan (TRP) and their metabolites' concentrations/levels: kynurenine (KYN), kynurenic acid (KYNA) and anthranilic acid (AA). The subjects were evaluated before and after weeks 2, 4, 8, 12, 24, 48, as well as 6 months after the end of the treatment. Results: In the group of patients treated 24 weeks, six months after the end of treatment IDO activity was significantly higher compared to baseline (69.5 vs 57.2 β = 0.21 P = 0.000); TRP concentration was significantly lower compared to baseline (30.0 vs 35.6 β=-0.21 P = 0.001); KYNA concentration was significantly higher compared to baseline (37.2 nmol/L vs 29.4 nmol/L β = 0.22 P = 0.02), and AA concentration was significantly higher compered to baseline (51.0 nmol/L vs 38.4 nmol/L β = 0.22 P = 0.05) In the group of patients treated 48 weeks six months, after the end of treatment both the IDO activity and KYNA concentration were significantly higher compared to baseline (respective values – IDO: 78.8 vs 56.2 β = 0.14 P = 0.02; KYNA: 39.2 nmol/L vs 27.0 nmol/L β = 0.26 P = 0.000). Conclusions: This is the first report of a prolonged activation of IDO six months after the end of PEG-IFN-α2a treatment. The clinical significance of the finding can be implicated in the pathophysiology of depressive episodes.